SIKAP INTERAKSI SOSIAL DAN INDIVIDU DALAM KEHIDUPAN SEHARI-HARI - Wahyuningsih, Sri (DIDAKTIK, 2011)
Abstract. The social interaction will happen when two people meet. At the time they may greet each other, hand shake, talk to each other or even fight. Such activities are kind of social interaction. Everyone has their own uniqueness and characteristic, there is no people precisely same.Key Words:Â  Social interaction, Human uniqueness.